Heavy Fuel: Trade and Environment in the GATT/WTO Case Law. Issue 3 (18th November 2014) - Cosbey, Aaron; Mavroidis, Petros C.
<x xml:space="preserve">Abstract</x> This article discusses the evolution of case law regarding the treatment of cases that the authors qualify as 'trade and environment' in the case law of the General Agreement on Tariffs and Trade (GATT) and the World Trade Organization (WTO). The main argument is that, as in many domestic jurisdictions, GATT/WTO courts moved from an original 'hostile' position towards environmental protection that incidentally affected trade flows to a more nuanced, even friendly attitude towards those measures that were legitimately 'green'. WTO courts, like other courts before them, saw the signs of times. They did not have to 'make' law, though, in order to change their attitude towards environmental concerns. They only had to correct a clear mistake they committed in the late 1980s in the notorious tuna‐dolphin dispute, and start interpreting the GATT/WTO as it was meant to be by its framers: societal preferences, to the extent they are non‐discriminatory, trump obligations to liberalize trade.